Antifungal Drugs for Invasive Candida Infections (ICI) in Neonates: Future Perspectives - Iliana Bersani; Fiammetta Piersigilli; Bianca Maria Goffredo; Alessandra Santisi; Sara Cairoli; Maria Paola Ronchetti; Cinzia Auriti (Frontiers Media S.A., 2019)
Fungal infections may complicate the neonatal clinical course, and the spectrum of therapies for their treatment in the perinatal period is limited. Polyenes, Azoles and Echinocandins represent the three classes of antifungal drugs commonly used in the neonatal period. The present review provides an overview about the most recent therapeutic strategies for the treatment of fungal infections in neonates.